Corporate Financial Reporting and Investors' Confidence in Listed Companies in Nigeria - Tamunokonbia Promise Ogan; Folajimi Festus Adegbie (CV ODIS, 2022)
With the recent reports of financial crisis, financial scandal and corporate failure there has been loss of investors’ confidence on corporate entities and the capital market in general. The study therefore investigated the impact of corporate financial reporting on investors’ confidence. The study adopted the ex-post facto research design using data from annual financial reports of the study population. The population consists of listed manufacturing companies in Nigeria as at December 31, 2020. The research data which was collected from the annual reports of ten manufacturing firms was analyzed with the aid of Eviews. Investors’ confidence was measured using Tobin’s Q while corporate financial reporting was measured using earnings management as proxy. The study revealed that corporate financial reporting has a significant positive influence on investors’ confidence (F-stat. = 24.0918; P = 0.0000). However, with the introduction of audit quality as moderating variable, the study showed that corporate financial reporting has a significant negative influence on investors’ confidence (F-stat. = 27.7559; P = 0.0000). Based on the result of the study, it was concluded that corporate financial reporting can contribute significantly to enhance influence on the investors’ confidence in Nigeria and audit quality could be employed to strengthen this relationship. The study recommends that firms and stakeholders of the accounting profession should continue to institute measures that will help enhance the quality corporate financial reporting as an essential tool to enhance investors’ confidence at both the micro and macro levels.